The role of work discipline in enhing lecturer performance in indonesian aviation higher education - Dede Ardian (Institute of Computer Science (IOCS), 2026)
This research examines the impact of work discipline on the performance of lecturers at the Akademi Penerbang Indonesia (API) Banyuwangi. A quantitative approach was employed, using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate data gathered from 19 lecturers via structured questionnaires. The results indicate that work discipline has a positive and statistically significant effect on lecturer performance. However, the model accounts for only a small fraction of the variance, implying that other factors also influence performance outcomes. These findings highlight the necessity of reinforcing disciplinary practices as part of comprehensive human resource management strategies to improve institutional effectiveness, especially in vocational aviation education.